2005
DOI: 10.1002/adma.200400155
|View full text |Cite
|
Sign up to set email alerts
|

Template Synthesis of Sc@C82(I) Nanowires and Nanotubes at Room Temperature

Abstract: The use of natural biological materials as templates to construct novel hierarchical inorganic materials is an emerging area due to their unique and complex microstructures. [1] Compare to artificial templates, biological materials are hierarchical, abundant, complex, renewable, and environmentally benign. So far, several types of biological materials such as diatoms, [2] bacteria, [3,4] pollen, [5] cornstarch, [6] chitin, [7] and wood [8,9] have been utilized in order to prepare hierarchical inorganic materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Among various methods of 1‐D nanowire synthesis, the anodic alumina template based routes have received considerable attention due to its several unique structural properties, such as controllable pore diameter, extremely narrow pore size distribution, and ideally cylindrical pore shape 65, 74–78. There have been several attempts to fabricate CNT based 1‐D core‐shell hybrid nanostructures using different techniques, such as electrochemical deposition, sol–gel, electroless deposition, CVD, and pressure injection.…”
Section: Synthesis Of Hybrid Nanostructuresmentioning
confidence: 99%
“…Among various methods of 1‐D nanowire synthesis, the anodic alumina template based routes have received considerable attention due to its several unique structural properties, such as controllable pore diameter, extremely narrow pore size distribution, and ideally cylindrical pore shape 65, 74–78. There have been several attempts to fabricate CNT based 1‐D core‐shell hybrid nanostructures using different techniques, such as electrochemical deposition, sol–gel, electroless deposition, CVD, and pressure injection.…”
Section: Synthesis Of Hybrid Nanostructuresmentioning
confidence: 99%
“…2,3 For mono-EMFs which contain only one metal atom, Wang et al fabricated nanotubes of Sc@C 82 with an anodic aluminum oxide template followed by electrochemical deposition in 2005. 4 In 2008, Tsuchiya et al obtained needlelike structures of La@C 82 (Ad) with a liquid−liquid interface precipitation (LLIP) method, which showed a p-type fieldeffect transistor (FET) property. 2 For cluster−EMFs (metallic clusters encapsulated in fullerenes), Sc 3 N@C 80 nanorods and nanosheets were first prepared by Wakahara et al in 2010, 5 and then in 2014, Xu et al reported the preparation of threedimensional (3D) nanostructures of Sc 3 N@C 80 via a microwave-assisted LLIP method.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To this end, ordered nano-/microstructures are normally necessary to achieve the corresponding applications. However, investigations of nanostructures of EMFs and their applications are quite limited up to now. , For mono-EMFs which contain only one metal atom, Wang et al fabricated nanotubes of Sc@C 82 with an anodic aluminum oxide template followed by electrochemical deposition in 2005 . In 2008, Tsuchiya et al obtained needlelike structures of La@C 82 (Ad) with a liquid–liquid interface precipitation (LLIP) method, which showed a p-type field-effect transistor (FET) property .…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory has been devoted to the study of fullerene and metallofullerene nanomaterials in the last decades [16,17], in particular the metallofullerene particles in different forms [18][19][20][21]. As motivated by a recent study on the synthesis of water soluble Gd@C 60 crystalline particles with a simple solid-liquid reaction [22], we prepared similar crystalline Gd@C 82 (OH) m nanoparticles using this novel technique.…”
Section: Size-expansible Phase Transition Of Rf-assisted Gfncsmentioning
confidence: 99%